Reinterpreting female identity in selected African male writers through ecofeminism - Muhammad, Nasiru Umar (2017)
The study explores the pattern of female portrayal in selected male African writings through the lens of ecofeminism with a view to analyzing a transformation in the pattern which gives rise to a new identity for the African woman. The study into the African female identity provides a key to the understanding of special qualities in contemporary writings by African male writers in relation to the plight of women. The study is set to debunk the generalization that male African writers are predominantly patriarchal in their writings. It is argued that there are male African writers that have been writing with women on their agenda. Fundamentally, the study proposes that female identity has been reinterpreted through a conscious effort in male – authored novels from the African continent. The researcher, therefore, utilizes ecofeminism as a theory that shows the interconnectedness between the exploitation of women and the degradation of natural environment as an analytical tool. This aims at studying the socio-economic conditions of the rural African women and how their lives are affected by the rupture of their natural environment upon which they rely for their sustenance. Using six novels by three African writers, two novel for each writer, (Ngugi wa Thiong’o’s Petals of Blood, and Wizard of the Crow; Chinua Achebe’s Girls at War, and Anthills of the Savannah, and Abubakar Gimba’s Witnesses to Tears and Sacred Apples), the study concludes that the neo-colonial misadventure in the continent have exposed both the environment and women to excessive exploitation. The study finally suggests the need for new environmental policies to save both the environment and the African women. This will in turn give women socio-economic independence and a new identity.